Policy Analysis Towards Karimunjawa Fisherman Catching Activity Regency Jepara - Bambang Argo Wibowo; Herry Boesono; Aryo Bayu Aditomo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
Karimunjawa National Park has pioneered in community development activities either through economic development, institutional strengthening, creation of alternative livelihoods and community  capacity building since 1998. This activity was expected to raise the public's readiness to participate in maintaining and preserving the Karimunjawa National Park. However, the participation in this context could place people as an object, not as a subject. Therefore, further study is needed on whether the conservation of biological diversity embodied in the Karimunjawa National Parks zoning really gave positive impact on  fishing communities and ecological sustainability. Moreover, fishermen only operate around coral reefs in shallow waters, making it very vulnerable to the violation of the National Park system zoning. The research method used in this research was descriptive method, while the sampling method used is purposive sampling. Data analysis methods used were SWOT and AHP analysis (Analytical Hierarchy Process). Policy strategies  to overcome the issue of the National Parks zoning is increased security in Karimunjawa conservation areas, increased cooperation between the BTN, DKP, and Tourism Department to maintain the potential of coral reef fishery resources in order to remain sustainable, the  allocation  of  funds  from  the  government  to  assist  BTN  monitored  overfishing,  illegal  fishing  ,  and environmental  pollution  from  damaged  fishing  gear,  and  the  provision  of  an  integrated  socialization  to encourage people to keep conserving the resources.   Key words: Karimunjawa National Park zoning, biodiversity conservation, AHP (Analytical Hierarchy Process)